(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2016)
Poverty and food shortage form the basis of food insecurity in the world, and this is well pronounced in sub-Sahara Africa where most farming households live on less than US1.25perday. A multistage random sampling procedure was used to select and interview 276 households. Data collected were analysed through the use of descriptive statistics, Foster, Greer and Thorbecke (FGT, 1984) poverty and food insecurity indices and Multinomial logit regression model.The study revealed that most of the respondents were older and aged between 51-60 years with a mean age of 55 years. Most of the farmers were married 79.85%, the mean households size was approximately 7 members. Also, during post harvesting season, households size (1%), home food production 1% and food-away-from-home 1% were positively significant which implied that a unit increase in households size, home production and food-away-from home, the probability of households to be food insecure/non-poor, food insecure/poor respectively will increase relative to food secure/non-poor, while in postplanting season, households size 1%, income 1%, farm size 5%, infrequently non-food expenditure 1% and food-away-from-home 1% were significant, this implied that in a unit increase in households size, income, infrequent non-food expenditure and food-away-from home, the probability of households to be food insecure/non-poor, food insecure/poor respectively will increase relative to food secure/non-poor. The study concluded that male headed households with small holding farm size, spending much on food-away-from-home and too much non-food expenditure might lead to food insecurity and poverty in the study area.